Neurobehavioural Correlates of Abnormal Repetitive Behaviour - R. A. Ford (Behavioural Neurology)
Conditions in which echolalia and echopraxia occur are reviewed, followed by an attempt to elicit possible mechanisms of these phenomena. A brief description of stereotypical and perseverative behaviour and obsessional phenomena is given. It is suggested that abnormal repetitive behaviour may occur partly as a result of central dopaminergic dysfunction.